Lackof lactobacillus sp in the vaginal flora during the labor of women endingin preterm deliveries - Giraldo, Paulo César; Fachini, Ana Maria D; Pereira, Renata TG; Pereira, Silvio; Nowakonski, Angela Von; Passos, Mauro Romero L (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: Little or nothing has been investigated about the association between preterm labor (PTL) and bacterial vaginosis (BV) during the moment oflabor. More relevant than the presence of BV might be the presence of the protective Lactobacillus sp in the vaginal flora. Objective: to quantify and comparethe presence of the Lactobacillus sp. and BV in women in PTL. Methods: pregnant women in confirmed PTL were sampled in order to obtain vaginal contentfor microbiologic analysis. Only patients hospitalised to inhibit labor were accepted in the study. Any other pregnant woman undergoing term labor makes upthe control group. Vaginal content was collected and placed on two glass slides for microbiologic analysis under optic microscopy. Results: abnormal flora(type 3) was found in 28 women from the total amount of studied cases (24.5%), where 18 (34.61%) belonged to the PTL group and only 10 (16.1%) to the termlabor (TL), p=0.02. BV was present in 13 women of the total (11.4%), being 9 (17.3%) among the PTL group and only 4 (6.4%) from TL group (ns). Onehundred and four women delivered and 10 are still pregnant or gave birth in other institutions. Conclusion: there is a strong association between the lack ofLactobacillus sp and TPP when the diagnoses are done during the labor. BV was 2.7 times more frequent in the cases of PTL when compared to TL.